Glucosyltransferase B/C expression in Streptococcus mutans of rampant and caries-free children - Yetty Herdiati H. Nonong (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2009)
Background: Streptococcus mutans (S. mutans) as specific bacteria causing dental caries have cariogenic characteristic related to glucosyltransferase (gtf) B/C that can change sucrose into insoluble glucan. Insoluble glucan functions as an attachment media and bacteria colonization, and also as a source of extracellular polysaccharide which is needed for the bacteria and may lead to caries formation. Purpose: The aim of this study was to find out the gtf B/C expression in isolated S. mutans from dental plaque of rampant and caries-free children. Methods: An observational study was done on 96 isolated bacteria grown in sucrose and bacitracin containing media, which include S. mutans INA 99, S. Mutans EU3, S.mutans EU7, S.EU10a, and S.mutans 10b. PCR technique was used as amplification technique for gtf B/C. Result: This study showed that gtf B/C gene was found in S. mutans, S. constellatus, S. bovis, S. anginosus, L. fermentum, L. salivarius, and Kleibsiella oxytoca. The presence of gtf B/C gene was found in 9 of 10 samples identified in the sample of rampant caries children. Conclusion: The gtf B/C enzyme was found not only in S. mutans, but also in other bacteria.